Assess your plant’s true water-savings potential - Abdul Manan, Zainuddin; Wan Alwi, Sharifah Rafidah; Samingin, Mohd Hisham; Misran , Norrazi (2006)
For companies in the chemical process industries, water is an indispensable utility. But the growing scarcity of quality industrial water, combined with stricter environmental regulations and the rising cost of wastewater treatment, have encouraged the conservation of water as a key utility in process plants. Concurrently, the development of systematic techniques for water reduction has made significant progress.